1988
DOI: 10.1038/bjc.1988.163
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo analysis of the effects of recombinant human granulocyte colony-stimulating factor in patients

Abstract: Summary Twelve patients with small cell lung cancer were treated with recombinant human granulocyte colony-stimulating factor, rhG-CSF, given by continuous infusion at doses ranging from 1 to 40 ig kg-'day-'. Patients received the rhG-CSF before the start of intensive chemotherapy and after alternate cycles of chemotherapy. Several in vitro assays were performed using peripheral blood neutrophils and marrow progenitor cells collected from patients prior to and after infusion of the growth factor. Peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(64 citation statements)
references
References 21 publications
3
61
0
Order By: Relevance
“…The potential for nephrotoxicity from the high kidney dose and the potential cross-fire effects from kidney to marrow are currently being assessed. Although bone marrow is usually the dose-limiting organ with current RAIT techniques (e.g., nuclides, chelates), the radiation dose to lungs, kidney and liver may make them critical sites (Brochud et al, 1988). In addition to our observations reported here, other investigators have shown, in animal experiments and clinical trials of RAIT, that the radiation dose to liver can be quite high (Langmuir and Sutherland, 1988;Buchsbaum et al, 1990).…”
Section: Discussionsupporting
confidence: 47%
“…The potential for nephrotoxicity from the high kidney dose and the potential cross-fire effects from kidney to marrow are currently being assessed. Although bone marrow is usually the dose-limiting organ with current RAIT techniques (e.g., nuclides, chelates), the radiation dose to lungs, kidney and liver may make them critical sites (Brochud et al, 1988). In addition to our observations reported here, other investigators have shown, in animal experiments and clinical trials of RAIT, that the radiation dose to liver can be quite high (Langmuir and Sutherland, 1988;Buchsbaum et al, 1990).…”
Section: Discussionsupporting
confidence: 47%
“…84 The GM-CSF-induced leukocytosis which increased in magnitude after repeated administration was due White blood cell subsets and neutrophil kinetics to increased numbers of eosinophilic and neutrophilic granulocytes and monocytes. [85][86][87] Bone marrow cellularity and Administration of pharmacological doses of G-CSF and GM-CSF to humans or animals resulted in a triphasic response: [70][71][72][73][74][75][76][77] (1) myeloid/erythroid ratios also increased during GM-CSF therapy. 76,85 In patients with congenital, cyclic and chronic neuMarket neutropenia occurring approximately 5-60 min after injection (depending on the mode of administration); (2) Leutropenias, G-CSF treatment was more effective in increasing the ANC than treatment with GM-CSF.…”
Section: Effects Of Pharmacological Doses Of G-csf and Gm-csf Onmentioning
confidence: 99%
“…This is true for G-CSF-induced neutrophils from patients with severe congenital neutropenia 107,108 and glycowith cancer and healthy volunteers have shown a decreased migration 70,72,[91][92][93] which was related to the dose of G-CSF in genosis type IB (GSD IB) 11,14,109 which have been described to show moderate to severe impairment of their chemotactic one study. 70 During continuous intravenous infusion of GM-CSF, a markedly reduced neutrophil motility was found in a response towards a variety of chemoattractants in vitro.…”
Section: Impaired Chemotaxis Prior To G-csfmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelosuppressive effects of chemotherapy can be mitigated in part by use of recombinant haemopoietic growth factors which stimulate the proliferation and maturation of haemopoietic cells in the bone marrow (Bronchud et al, 1988;Groopman et al, 1989;Hermann et al, 1989). One of these factors, rG-CSF, stimulates granulocyte proliferation in vivo (Souza et al, 1986;Cullor et al, 1990) and when given by continuous intravenous infusion, can reduce the duration of neutropenia in patients with chemotherapy induced myelosuppression (Bronchud et al, 1987; Recombinant human granulocyte stimulating factor (rG-CSF) was supplied by Chugai Pharmaceutical Company, Japan.…”
mentioning
confidence: 99%